Synthesis and Properties of Oligonucleotides Containing LNA-Sulfamate and Sulfamide Backbone Linkages - Zengin Kurt, B; Dhara, D; El-Sagheer, AH; Brown, T (American Chemical Society, 2024)
Oligonucleotides hold great promise as therapeutic agents but poor bioavailability limits their utility. Hence, new analogues with improved cell uptake are urgently needed. Here, we report the synthesis and physical study of reduced-charge oligonucleotides containing artificial LNA-sulfamate and sulfamide linkages combined with 2′-O-methyl sugars and phosphorothioate backbones. These oligonucleotides have high affinity for RNA and excellent nuclease resistance.